Kejahatan Korporasi dalam Kasus Bantuan Likuiditas Bank Indonesia (BLBI): Analisis Yuridis terhadap Penyimpangan, Pertanggungjawaban Hukum, dan Dampaknya terhadap Keuangan Negara - Nur`ainy Agmilya Sasmitha; Rahayu Sri Utami (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The Bank Indonesia Liquidity Assistance (BLBI) case represents one of the most significant corporate crime cases in Indonesia’s banking history, revealing complex interactions between regulatory weaknesses, corporate misconduct, and state financial losses. This study examines corporate crime in the BLBI case through a juridical analysis focusing on deviations in fund utilization, legal accountability mechanisms, and their impact on state finances. The findings indicate that the misuse of BLBI funds was facilitated by inadequate banking supervision, weak corporate governance, and ineffective enforcement of prudential principles during the financial crisis. Although Indonesian law provides a framework for corporate criminal liability and asset recovery, practical implementation has faced substantial legal and institutional challenges. The BLBI case has caused not only massive financial losses to the state but also long-term consequences for public trust in the banking system and legal institutions. Therefore, strengthening legal accountability, enhancing transparency, and reforming banking supervision are essential measures to prevent similar corporate crimes and to safeguard state financial interests in the future.